Proteomic analysis of the effect of extracellular calcium ions on human mesenchymal stem cells: Implications for bone tissue engineering. (25th May 2015) - Lei, Qun; Chen, Jiang; Huang, Wenxiu; Wu, Dong; Lin, Hengzhang; Lai, Yingzhen
Graphical abstract: Highlights: We explore the molecular mechanism by coupling iTRAQ with nano-LC–MS/MS. Ca 2+ could induce osteogenic differentiation of BM-hMSCs in serum-free medium. MAPKs pathway might participate in the osteogenic differentiation of BM-hMSCs. Some novel proteins were discovered in osteogenic differentiation of BM-hMSCs. Abstract: Human mesenchymal stem cells-bone marrow (BM-hMSCs) are considered as the most suitable seed cells for bone tissue engineering. Calcium ions (Ca 2+ ) forms an important component of a number of commercial bone substitutes and support materials. For efficient bone tissue engineering, it is crucial to explore the effect of extracellular Ca 2+ on the growth and differentiation of BM-hMSCs, and to understand their molecular mechanisms. Therefore, in the present study, BM-hMSCs were cultivated in serum free growth medium or serum free growth medium with additional 4 or 6 mM Ca 2+ for 3 weeks, following which, the proliferation and osteoblastic differentiation of these cells were evaluated. Differentially expressed proteins were established using iTRAQ labeling coupled with nano-LC–MS/MS. Our data revealed that Ca 2+ significantly promoted the proliferation of BM-hMSCs in the early stage. Furthermore, Ca 2+ showed osteoinduction properties. MAPKs signaling pathway might participate in the osteogenic differentiation of BM-hMSCs caused by Ca 2+ . Certain newly found proteins could be potentially important for the osteogenic differentiation of BM-hMSCs and may be associated with osteogenesis.